Aktywność edukacyjna osób starszych jako predykator pomyślnego starzenia się - WIŚNIEWSKA, JOLANTA IZABELA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Jolanta Izabela Wiśniewska, Educational activity of seniors as a predictor of successful ageing, Interdisciplinary Contexts of Special Pedagogy, No. 22, Poznań 2018. Pp. 27–45. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.03 The article presents a paradigmatic change taking place in the theoretical approach to adult education. Against this background and in the context of contemporary conditions, the author points to the importance of learning from everyday experience and the role of educational activity in this process. The discussed issues were focused on the elderly.